Reinterpreting Faith in the Modern World: A Sociological Analysis of Evolving Religious Practices and Beliefs - Miftahul Ulum (International Journal of Sociology of Religion, 2023)
This article discusses a reinterpretation of confidence in the modern world: a sociological analysis of the development of religious practices and beliefs, how religious convictions and practices are viewed in a sociological lens in a constantly changing society. With this approach, the author will study how the relationship between religion and modern social dynamics is developing, as well as recognizing the challenges and opportunities faced by religious communities in an increasingly integrated global context, it USES library studies that involve in-depth analysis of literature, publications, and other relevant written sources on the research topic. What this article concluded is that it presents a deep insight into the dynamics of the relationship between religion, society, and the changing times. In the face of global change, recognition of the complexity of religious interpretation and openness to change becomes the key to maintaining relevance and sustainability of religious practice and belief in the ever-expanding modern age.